Perception Of Socialization In Interprofessional Practice Among Healthcare Professionals At Tertiary Healthcare Facility - Khadija Qamar; Abdullah Azam Khan; Taimur Azam Khan; Anam Haider; Rehana Khadim; Tahira Ayub (Journal of Rawalpindi Medical College)
Objective: To analyze the perceptions of health care professionals from a variety of fields (Anesthesia, Radiology, Gynecology, Surgery, and Orthopedics) on inter-professional socialization in a clinical setting to determine any potential disparities between educational training and to identify gaps.